1994
DOI: 10.3109/01480549409064046
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of teratogenic potential of khat (catha edulis forsk.) In rats

Abstract: The embryotoxic and teratogenic effects of khat (Catha edulis Forsk.), a plant chewed by the people of Eastern Africa and Southern Arabia to attain a state of euphoria and stimulation, was studied in Wistar rats. Methanolic extract of khat was administered orally by gavage to rats during days from 6 to 15 of gestation at doses of 0, 125, 250 and 500 mg/kg. body weight/day. Khat reduced the food consumption and maternal weight gain and also lowered the food efficiency index, as compared to control mothers. On d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
28
1

Year Published

1999
1999
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(31 citation statements)
references
References 23 publications
2
28
1
Order By: Relevance
“…Retardation of growth rate was considered to be due to decreased absorption of food and not to decreased food consumption. In pregnant rats, khat reduced food consumption and maternal weight gain [18,26]. Many reports have confirmed enhanced locomotor activity with enhanced baseline aggressivity of isolated rats [27].…”
Section: Animal Studiesmentioning
confidence: 93%
“…Retardation of growth rate was considered to be due to decreased absorption of food and not to decreased food consumption. In pregnant rats, khat reduced food consumption and maternal weight gain [18,26]. Many reports have confirmed enhanced locomotor activity with enhanced baseline aggressivity of isolated rats [27].…”
Section: Animal Studiesmentioning
confidence: 93%
“…However, during the same period, the dose of 25 mg/kg dose did not affect this index. At the advanced stage of gestation (days [15][16][17][18][19][20] only the high dose of PZA (500 mg/kg) led to a significant decrease in the FEI compared to the control group. This dose (500 mgikg) also caused significant (P < 0.05) reduction (88.8%) in the growth index which is calculated as the mean weight/pup/litter X mean CRL/pup/litter X litter size divided by 100.…”
Section: Methodsmentioning
confidence: 86%
“…The ovaries and uteri were removed by a cesarean section and fetal toxicity was assessed as described in previous studies [3,18]. The number of viable and non-viable fetuses, resorptions, implantations, and corpora lutea were recorded.…”
Section: Methodsmentioning
confidence: 99%
“…The second study, on the other hand, reported an increased incidence of oral cancer among 25 long term khat users who were non-smokers residing in the Asir area of Saudi Arabia [10] . There is evidence that hydrolizable tannins, which are present in high amounts in khat leaves [16] may contribute to the cytotoxic, genotoxic and clastogenic effects. Tannins are defined as water-soluble polymeric phenolics that precipitate proteins.…”
Section: Discussionmentioning
confidence: 99%